2006
DOI: 10.1124/jpet.106.107557
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 Receptor Activation Prevents Intracellular Calcium Dysregulation in Cortical Neurons during in Vitro Ischemia

Abstract: Sigma receptors are putative targets for neuroprotection following ischemia; however, little is known on their mechanism of action. One of the key components in the demise of neurons following ischemic injury is the disruption of intracellular calcium homeostasis. Fluorometric calcium imaging was used to examine the effects of sigma receptor activation on changes in intracellular calcium concentrations ([Ca 2ϩ ] i ) evoked by in vitro ischemia in cultured cortical neurons from embryonic rats. The sigma recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 37 publications
9
96
1
Order By: Relevance
“…In vitro studies revealed potent neuroprotective effects of sigma-1R agonists after excitotoxic damage [18], hypoxia-mediated neurotoxicity [41], oxidative stress-induced cell death [17], or glucose deprivation [42]. In vivo studies demonstrated that sigma-1R agonists exert therapeutic actions in rats after stroke [19,20], after selective cholinergic lesions [43], and after spinal root avulsion [10].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies revealed potent neuroprotective effects of sigma-1R agonists after excitotoxic damage [18], hypoxia-mediated neurotoxicity [41], oxidative stress-induced cell death [17], or glucose deprivation [42]. In vivo studies demonstrated that sigma-1R agonists exert therapeutic actions in rats after stroke [19,20], after selective cholinergic lesions [43], and after spinal root avulsion [10].…”
Section: Discussionmentioning
confidence: 99%
“…Primary cortical neurons from embryonic (E18) rats were cultured as previously described by our laboratory (Katnik et al, 2006). All procedures were done in accordance with the regulations of the University of South Florida Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…All of these voltagegated ion channels and NMDA receptors have been shown to contribute to the demise of neurons during an ischemic insult. Our laboratory has recently shown that -1 receptors inhibit Ca 2ϩ dysregulation evoked by ischemia and that activation of receptors is neuroprotective at delayed time points in a rat model of ischemic stroke (Ajmo et al, 2006;Katnik et al, 2006). Interstitial pH in the brain remains low several hours after an ischemic event (Nedergaard et al, 1991), and pharmacological blockade of ASIC1a by amiloride or psalmotoxin1 administered even 5 h after middle cerebral artery occlusion has been shown to diminish stroke injury (Simon, 2006).…”
mentioning
confidence: 99%
“…There are several factors that contribute to neuroprotective ability of sigma receptors. Sigma-1 receptor's ability to bind and associate with L-type voltage gated calcium channels, regulate neuronal intracellular calcium concentrations when exposed to ischemic conditions, prevent glutamate excitotoxicity of RGCs when exposed to sigma-1 agonist (+)-pentazocine are some of the key mechanisms underlying sigma-1's neuroprotective effects Katnik at al., 2006;Dun et al, 2007). Other pathways affected by sigma-1 receptor include attenuation of intrinsic death signal of glutamate-exposed retinal cell lines, which is a likely candidate to maintain the viability, and homeostatic intracellular calcium regulation of RGCs when they are exposed to a number of noxious stimuli that cause RGC apoptosis .…”
Section: Sigma-1 Receptormentioning
confidence: 99%